2018
DOI: 10.1007/s00436-018-6068-3
|View full text |Cite
|
Sign up to set email alerts
|

Agents of swimmer’s itch—dangerous minority in the Digenea invasion of Lymnaeidae in water bodies and the first report of Trichobilharzia regenti in Poland

Abstract: Trichobilharzia spp. have been identified as a causative agent of swimmers’ itch, a skin disease provoked by contact with these digenean trematodes in water. These parasites have developed a number of strategies to invade vertebrates. Since we have little understanding of the behavior of these parasites inside the human body, the monitoring of their invasion in snail host populations is highly recommended. In our research, lymnaeid snails were collected from several Polish lakes for two vegetation seasons. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 75 publications
(102 reference statements)
1
8
0
Order By: Relevance
“…The less frequent use of S. palustris by bird schistosomes is also confirmed by the fact that in the research presented only one infected individual of this host species was found. The prevalence of bird schistosomes we found in both L. stagnalis and P. corneus is comparable to the results of previous studies (Loy and Haas, 2001;Żbikowska, 2004;Falt ynková, 2005;Falt ynková and Haas, 2006;Falt ynková et al, 2007;Soldánová et al, 2010;Marszewska et al, 2016;Marszewska et al, 2018). However, it should be noted that Marszewska et al (2016) observed a lower prevalence of B. polonica (2.9%) in host snails from the Polish water body, as did Żbikowska (2007), who described the occurrence of B. polonica in three out of 29 water bodies where the prevalence of this parasite in P. corneus fluctuated from 1% to 2%.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The less frequent use of S. palustris by bird schistosomes is also confirmed by the fact that in the research presented only one infected individual of this host species was found. The prevalence of bird schistosomes we found in both L. stagnalis and P. corneus is comparable to the results of previous studies (Loy and Haas, 2001;Żbikowska, 2004;Falt ynková, 2005;Falt ynková and Haas, 2006;Falt ynková et al, 2007;Soldánová et al, 2010;Marszewska et al, 2016;Marszewska et al, 2018). However, it should be noted that Marszewska et al (2016) observed a lower prevalence of B. polonica (2.9%) in host snails from the Polish water body, as did Żbikowska (2007), who described the occurrence of B. polonica in three out of 29 water bodies where the prevalence of this parasite in P. corneus fluctuated from 1% to 2%.…”
Section: Discussionsupporting
confidence: 92%
“…in the results presented is probably associated with the relatively small sample of the tested individuals. Recent reports on outbreaks of swimmer's itch lack information on the presence of bird schistosomes in S. palustris specimens (Żbikowska, 2004;Marszewska et al, 2018). For example, in Poland, Cichy and Żbikowska (2016) described the only case of T. szidati larvae in this intermediate host.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This can be done by weekly collection of snails and performing shedding experiments as described here. It is known that snail size influence shedding capacity [14,36,37]. In our study, the experimental snails had a mean shell height of 44.6 (SD 6.3) mm it is worthwhile to monitor snail size and survival for future risk analyses of the lake.…”
Section: Discussionmentioning
confidence: 76%
“…The samples were gathered in September 2018, that is, after months of the strongest release of cercariae from the first intermediate hosts (various species of freshwater snails) (Marszewska et al, 2018b;Cichy et al, 2019) for which P. antipodarum can play the role of the second intermediate host (Żbikowski and Żbikowska, 2009;Cichy et al, 2017). The study areas which we used for the research were water bodies from three different parts of Poland: western Poland À Lake Czaplino; central À Lake Iławskie and Lake Sosno; and southern Poland À a pond in Strzemieszyce Wielkie (a district of Dąbrowa Górnicza), as well as a bathing resort in the Valley of Three Ponds area in Katowice (Fig.…”
Section: Research Area and Samplingmentioning
confidence: 99%